2014
DOI: 10.2147/ijn.s57925
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of colloidal silica nanoparticles administered orally for 90 days in rats

Abstract: This study was undertaken to investigate the potential toxicity and establish the no observed adverse effect level (NOAEL) and target organ(s) of negatively charged colloidal silica particles of different sizes, ie, SiO 2 EN20(−) (20 nm) or SiO 2 EN100(−) 2(100 nm), administered by gavage in Sprague-Dawley rats. After verification of the physicochemical properties of the SiO 2 particles to be tested, a preliminary do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In contrast, Kim et al . 25 reported that high-dose oral intake (2000 mg/kg) of 20- and 100-nm SiNPs for 90 days appeared to be relatively safe in rats. The inconsistency in the aforementioned findings on the oral toxicity of SiNPs could be explained by the results of previous studies, which found that the nanotoxicity of SiNPs was dependent on their size and dose, as well as the cell type 13 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kim et al . 25 reported that high-dose oral intake (2000 mg/kg) of 20- and 100-nm SiNPs for 90 days appeared to be relatively safe in rats. The inconsistency in the aforementioned findings on the oral toxicity of SiNPs could be explained by the results of previous studies, which found that the nanotoxicity of SiNPs was dependent on their size and dose, as well as the cell type 13 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…[69][70][71][72] The NPs used in our study were also found to be capable of producing intracellular ROS with increased lipid peroxide levels. The LPO produced more free radicals, which could damage biomolecules, such as DNA, proteins, and lipids in combination with ROS.…”
mentioning
confidence: 54%
“…SiO 2 NPs led to the destruction of the intestinal epithelial layer and liver fibrosis [ 6 , 65 ]. However, other studies showed SiO 2 NPs have no impact on the gut, deeming them safe for use in foods [ 66 , 67 ]. TiO 2 NP treatment led to the irregular arrangement of epithelial cells, increased length of intestinal villi, intestinal inflammation, and preneoplastic lesions [ 59 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, other studies have found silica to have no effect on the gut. Colloidal silica particles, differing in size (20 nm and 100 nm), were orally administered to Sprague-Dawley rats [ 66 ]. A ninety-day repeated dose (2000 mg/kg, 1000 mg/kg or 500 mg/kg) study was conducted.…”
Section: Impact Of Inorganic Food Nanoparticles On the Gastrointesmentioning
confidence: 99%